Nurses’ Knowledge Regarding Contraceptive Methods at Dinajpur Medical College Hospital - Most Morsheda Parvin; M F K Al Mannah; Esrat Jahan Sathi (Randwick International of Social Science Journal, 2021)
This study was carried out on Nurses Knowledge Regarding Contraceptives Methods in Dinajpur Medical college Hospital, Dinajpur. The descriptive co relational design was used to explore the nurse’s knowledge and practice regarding contraceptives methods used in Dinajpur Medical college Hospital, Dinajpur. The study was conducted in thirty-two wards under four selected units, including 1) Gynae ward 2) Labour ward 3) Family planning centre. 50 nurses were selected for this study. The instrument developed by the researcher was divided into three sections, including 1) Demographic Questionnaire 2) Nurses’ knowledge regarding contraceptives methods Questionnaire 3) Nurses’ practice regarding contraceptives methods Questionnaire. The age of the participated nurses was 30-39 years 28%, 40-49 years 66%, 50+ above 4%. Of them, a male nurse was 12% and a female 88%. No unmarried nurse has participated, and 96% were married, and the remaining 4% were a widow. Professional qualification, Diploma in Nursing and Diploma in Midwifery 76%, B. Sc. in public Health 0%, M. Ph / M. Sc. 10%.